Exploring EFL Students’ Perceptions of Purposeful Listening Strategies in a Listening for Professional Context Course - Badu, Helena; Basalama, Nonny (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This article explores EFL students’ perceptions of purposeful listening strategies implemented in a Listening for Professional Context course at Universitas Negeri Gorontalo. This study used a convergent mixed-methods design; data sources were collected from 23 students in an English Language Education Study program through Likert-scale questionnaires, followed by open-ended reflections. Findings reveal that structured listening cycles were perceived to develop students’ focus, metacognitive awareness, strategic autonomy, and engagement with authentic listening materials, suggesting a perceived shift toward more active listening. Pre-listening activities facilitated mental readiness and reduced initial cognitive load, while-listening strategies promoted active processing and real-time monitoring, while post-listening reflection enhanced metacognitive awareness and learner autonomy. Students reported that listening tasks became more manageable and meaningful when guided by explicit strategies, even when working with authentic professional audio texts. These results underscore the importance of integrating purposeful listening cycles into EFL listening instruction, particularly in contexts employing authentic professional materials. The study is limited by a small sample size and reliance on self-reported data. However, it contributes context-specific insight into the use of purposeful listening cycles in the Listening for Professional Context course, with implications for EFL curriculum design and strategy-oriented listening instruction in higher education.